Elevated troponin level and nonspecific ST‐segment and T‐wave changes in a suspected acute pancreatitis patient, post‐SARS‐Cov‐2 infection: A case report - Pourfridoni, Mohammad; Khan, Moien A. B.; Khalil‐Khan, Alam; Mohammad Bagheri Rafsanjani, Afshin; Askarpour, Hedyeh (Clinical case reports, 2022)
The case report describes a post‐COVID‐19 patient with severe right upper quadrant (RUQ) pain, moderate epigastric pain, high troponin levels, and nonspecific ST‐segment and T‐wave changes on electrocardiogram (ECG). A possible association between altered cardiac biomarkers and ECG is demonstrated in the current report following acute pancreatitis or COVID‐19. Following the ruling out of cardiac causes, the usual management process for treating the underlying AP disease should be undertaken without delay.